HUBUNGAN PERILAKU IBU HAMIL DALAM PELAKSANAAN P4K DENGAN KESIAPAN IBU HAMIL MENGHADAPI KOMPLIKASI - Miftakhul Jannah; Reni Wahyu; Desy Dwi Cahyani; Lisa Purbawaning (Jurnal Pendidikan Kesehatan, 2021)
Pregnancy and childbirth complications are the leading causes of death among women of reproductive age worldwide. One of the government efforts to reduce MMR and IMR is through the Maternity Planning and Complications Prevention Program or P4K. The purpose of this study was to determine the relationship between the behavior of pregnant women in implementing P4K and the readiness of pregnant women to face complications. This research uses a cross sectional approach correlational study design. The number of samples in this study was 40 respondents with simple random sampling technique. The instrument used was a questionnaire. Data processing using computerization. The results of measuring the behavior of pregnant women in the implementation of P4K, most of the pregnant women had poor behavior, while the readiness of pregnant women to face complications, namely half of pregnant women were ready to face complications and the other half were not ready to face complications. pregnant women to improve their behavior in implementing P4K by always carrying out and being active in all activities related to P4K so that pregnant women have readiness to face the possibility of complications that may occur at any time